Personalização: um serviço mediador em ambientes de pesquisa - Camargo, Liriane Soares De Araújo De [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio (Pontifícia Universidade Católica de Campinas, 2007)
The large amount of information in digital environment makes it difficult to organize and retrieve such information. Customization resources can guide and recommend more specific information to specific kinds of users. In this context, a resource set that can help the websites developer/designer in the choice and implementation of these resources, as well as help the users in the search and acquisition of information is presented. Besides, it is presented how the customization can help in the communication process and scientific production in digital environment, showing its operation, features and benefits. The resources presented here were identified by means of an analysis in several types of websites. In the scientific literature few papers present options of customization techniques in unique conceptual base.

A grande quantidade de informações no ambiente digital dificulta a sua organização e recuperação. Recursos de personalização podem direcionar e recomendar informações mais específicas para determinado tipo de usuário. Nesse contexto, é apresentado um conjunto de recursos de personalização que podem auxiliar o desenvolvedor/projetista de websites na escolha e na implantação de tais recursos, bem como auxiliar os usuários na busca e na aquisição de informação. Além disso, apresenta-se também como a personalização pode auxiliar no processo de comunicação e produção científica em ambiente digital, mostrando seu funcionamento, características e benefícios. Os recursos de personalização foram identificados por meio de análise em websites comerciais e acadêmicos. Na literatura científica, poucos trabalhos apresentam opções de recursos de personalização em base conceitual única.
Personalization: a mediating service in research environments
Keywords: personalização; interação usuário-sistema; sistema de recomendação; ambientes de pesquisa; perfil de usuários; customization; user system interaction; recommendation system; research environment; user profile